A Fast Imaging Technique Applied to 2D Electrical Resistivity Data - Raffaele Martorana; Patrizia Capizzi (International Journal of Geophysics)
A new technique is proposed to process 2D apparent resistivity datasets, in order to obtain a fast and contrasted resistivity image, useful for a rapid data check in field or as a starting model to constrain the inversion procedure. In the past some modifications to the back-projection algorithm, as well as the use of filtering techniques for the sensitivity matrix were proposed. An implementation of this technique is proposed here, considering a two-step approach. Initially a damped least squares solution is obtained after a full matrix inversion of the linearized geoelectrical problem. Furthermore, on the basis of the results, a subsequent filtering algorithm is applied to the Jacobian matrix, aiming at reducing smoothness, and the linearized damped least square inversion is repeated to get the final result. This fast imaging technique aims at increasing the resistivity contrasts and practically, since it does not require a parameter set optimization, it can be used to easily obtain fast and preliminary results. The proposed technique is tested on synthetic data, the objective of which is to find the optimal parameter set. Finally, two field cases are discussed and the comparison between back-projection and inversion is shown.